Does immediate dentin sealing influence postoperative sensitivity in teeth restored with indirect restorations? A systematic review and meta‐analysis. Issue 1 (3rd December 2021) - Josic, Uros; Sebold, Maicon; Lins, Rodrigo B. E.; Savovic, Jelena; Mazzitelli, Claudia; Maravic, Tatjana; Mazzoni, Annalisa; Breschi, Lorenzo
Abstract: Objective: This study comprehensively reviewed clinical trials that investigated the effect of immediate dentin sealing (IDS) technique on postoperative sensitivity (POS) and clinical performance of indirect restorations. Materials and methods: The systematic review was conducted according to the preferred reporting items for systematic reviews and meta‐analyses statement, and was guided by the PICOS strategy. Clinical trials in which adult patients received at least one indirect restoration cemented with IDS approach and one restoration cemented following the delayed dentin sealing (DDS) were considered. Results: Following title screening and full‐text reading, four studies met the inclusion criteria and were included for qualitative synthesis, while two studies were selected for quantitative synthesis. According to Risk of bias‐2 tool, two studies were classified as "some concerns" for the outcome POS. No statistically significant differences were found between teeth restored with indirect restorations using the IDS and DDS approach for POS ( p  > 0.05), neither at the baseline (very low certainty of evidence according to GRADE) nor after 2 years of follow‐up (low certainty of evidence according to GRADE). Conclusion: There is low‐certainty evidence that IDS does not reduce POS in teeth restored with indirect restorations. Clinical significance: There is no clinical evidence to favor IDS over DDS when restoring teeth with indirect restorations.